Civil Identity as Ethical Self-Determination - Karas, Anatoliy (Filosofiya osvity. Philosophy of Education, 2013)
Civil identity is a societal construct of consciousness and communicative practices, the construal of public and private levels of social life emerging around the recognition of the values of individual freedom, dignity and uniqueness of human. It is influenced by the involvement of knowledge in the organization of social and economic development and is associated with the generation of cultural and emotional values and norms of everyday life. Civil identity exists as a discursive-ethical activity focused particularly on the person’s moral self-determination in the dealings with the community and society. Contemporary semiotic studies allow combining the development of the signs language and art representation with that of the physical senses and emotional perception of reality within one context of understanding. All human systems interact with the brain and are interdependent. Attention is drawn to fact that civil identity as ethical self-determination is congruent with the responsibility that exists in connection with the growth of civilization’s potential of empathy.